Profiles of patients with urinary incontinence in the Department of Child Health, Cipto Mangunkusumo Hospital - Eveline P N; Taralan Tambunan; Sri Rezeki S Hadinegoro (Paediatrica Indonesiana, 2005)
Background Urinary incontinence (UI) in children is a form ofwetting. Early diagnosis and treatment are mandatory to avoidcomplications such as recurrent urinary tract infections (UTI),vesicoureteral reflux (VUR), or renal damage.Objective To study the profiles and clinical course of UI in chil-dren treated in Cipto Mangunkusumo Hospital.Methods The study was divided into 2 parts. The first part was areview of patients with UI at Cipto Mangunkusumo Hospital fromJanuary 2000 to December 2003. The second was a case seriesof patients followed up for at least 6 months.Results There were 35 UI patients aged 3 months to 16 years,mostly between 1 to 5 years old, 16 were males and 19 females.The most prevalent etiology was myelodysplasia (15 cases) fol-lowed by posterior urethral valve, and bladder tumor. The mostprominent clinical presentation of neurophatic bladder-sphincterdysfunction was wetting, while those of patients with structural in-continence and non-neuropathic bladder-sphincter dysfunctionwere fever and polakysuria. Most patients had been suffering fromrenal insufficiency since their first visit. Clean intermittent catheter-ization (CIC) was the treatment of choice. In a six-month follow-upof 14 patients who received adequate treatment, renal functioncould be maintained at relatively stable condition in most cases.Conclusions Myelodysplasia was the most common etiology ofUI. Most patients had renal insufficiency or renal failure since theirfirst visit, reflecting a extended period of relapse before patientsseek medical help. Renal function can be maintained by adequatetreatment in most cases